2013
DOI: 10.1016/j.fertnstert.2012.12.048
|View full text |Cite
|
Sign up to set email alerts
|

Antimüllerian hormone in gonadotropin releasing-hormone antagonist cycles: prediction of ovarian response and cumulative treatment outcome in good-prognosis patients

Abstract: NCT00884221.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
122
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 28 publications
9
122
1
14
Order By: Relevance
“…OR of 0.3 can be interpreted as a 70 % reduction in low oocyte yield for each additional unit increase of AMH. This is consistent with prior studies in healthy populations demonstrating the predictive power of AMH for response to stimulation and ART outcomes [32,33]. Low AMH has been associated with poor response to stimulation and oocyte yield [34][35][36] and may also be useful information prior to starting the cycle.…”
Section: Discussionsupporting
confidence: 90%
“…OR of 0.3 can be interpreted as a 70 % reduction in low oocyte yield for each additional unit increase of AMH. This is consistent with prior studies in healthy populations demonstrating the predictive power of AMH for response to stimulation and ART outcomes [32,33]. Low AMH has been associated with poor response to stimulation and oocyte yield [34][35][36] and may also be useful information prior to starting the cycle.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings was different from other studies which had shown that AMH is the good predictor of ovarian response in GnRH antagonist cycles, but according to our results AFC was found to be a better predictor of ovarian response in patients undergoing GnRH antagonist cycle for having abnormal ovarian reserve. [15][16][17][18][19] A study done among the Vietnamese women had also shown AMH as the best predictor of ovarian response in GnRH antagonist cycle. 20 In the present study we found that the combination of biomarker particularly AFC+AMH was found to have statistical significant association in predicting the ovarian response, whereas the other biomarker combinations like AFC+FSH and AMH+FSH did not had a significant association in the ovarian response prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Few of the studies done by Arce et al and TNL Vuong et al have found that FSH was significantly less useful than AFC and AMH as a predictor of ovarian response and this was almost in par with our study, where among the poor responders in our study the FSH had the lowest predictive value when compared to AFC and AMH in predicting ovarian response. 16,20 While AFC and AMH are good predictors of ovarian response, they appear to have less value in predicting live birth rate. There are number of factors that determine the chance of pregnancy other than ovarian response including embryo quality, transfer technique and endometrial receptivity, which may be why tests for ovarian response may not be sensitive enough to predict pregnancy outcome after IVF/ICSI.…”
Section: Discussionmentioning
confidence: 99%
“…Since AFC is tied to AMH level and vice versa, a number of studies have compared AFC with AMH level as predictors of ovarian response in IVF. Three recent multicenter trials of good prognosis IVF patients showed that the AMH level was a better predictor of ovarian response than AFC in both gonadotropinreleasing hormone (GnRH) agonist and antagonist cycles [14][15][16]. In contrast, Mutlu et al (2013) conducted a prospective study which demonstrated that AFC determines p o o r o v a r i a n r e s p o n s e b e t t e r t h a n A M H [ 1 7 ] .…”
Section: Discussionmentioning
confidence: 99%